Broad diversity of simian immunodeficiency virus infecting Chlorocebus species (African green monkey) and evidence of cross‐species infection in Papio anubis (olive baboon) in Kenya. Issue 4 (6th February 2020) - Nyamota, Richard; Owino, Vincent; Murungi, Edwin Kimathi; Villinger, Jandouwe; Otiende, Moses; Masiga, Daniel; Thuita, John; Lekolool, Isaac; Jeneby, Maamun
Abstract: Background: Simian immunodeficiency virus (SIV) naturally infects African non‐human primates (NHPs) and poses a threat of transmission to humans through hunting and consumption of monkeys as bushmeat. This study investigated the as of yet unknown molecular diversity of SIV in free‐ranging Chlorocebus species (African green monkeys—AGMs) and Papio anubis (olive baboons) within Mombasa, Kisumu and Naivasha urban centres in Kenya. Methods: We collected blood samples from 124 AGMs and 65 olive baboons in situ, and detected SIV by high‐resolution melting analysis and sequencing of PCR products. Results: Simian immunodeficiency virus prevalence was 32% in AGMs and 3% in baboons. High‐resolution melting (HRM) analysis demonstrated distinct melt profiles illustrating virus diversity confirmed by phylogenetic analysis. Conclusions: There is persistent evolutionary diversification of SIVagm strains in its natural host, AGMs and cross‐species infection to olive baboons is occurring. Further study is required to establish pathogenesis of the diverse SIVagm variants and baboon immunological responses.